Biodegradable Polymeric Nanoparticles for Drug Delivery to Solid Tumors - Gagliardi, Agnese; Giuliano, Elena; Venkateswararao, Eeda; Fresta, Massimo; Bulotta, Stefania; Awasthi, Vibhudutta; Cosco, Donato (Frontiers in Pharmacology, 2021)
Advances in nanotechnology have favored the development of novel colloidal formulations able to modulate the pharmacological and biopharmaceutical properties of drugs. The peculiar physico-chemical and technological properties of nanomaterial-based therapeutics have allowed for several successful applications in the treatment of cancer. The size, shape, charge and patterning of nanoscale therapeutic molecules are parameters that need to be investigated and modulated in order to promote and optimize cell and tissue interaction. In this review, the use of polymeric nanoparticles as drug delivery systems of anticancer compounds, their physico-chemical properties and their ability to be efficiently localized in specific tumor tissues have been described. The nanoencapsulation of antitumor active compounds in polymeric systems is a promising approach to improve the efficacy of various tumor treatments.